A Comparative Analysis of Control Strategies for Low Harmonic Rectifier having a DC-DC Converter - Nwosu, Cajethan; Ogbuka, Cosmas; Oti, Stephen (Recent Advances in Electrical & Electronic Engineering, 2018)
Background: A comparative analysis of Sliding Mode Control (SMC) and conventional average current control (AvCC) of a single phase low harmonic rectifier (LHR) having a DC–DC converter is presented. Methods: The SMC which hitherto has been extensively deployed in the control of DC-DC converters is combined with an aspect of AvCC to effectively harness their individual benefits in the control of a LHR. Amongst the four control scenarios, the SMC scheme in which the SMC acts simultaneously on the controlled variables involving both the current and the voltage to generate the switching function by proper choice of sliding coefficients demonstrates a better performance in terms of robustness in the dynamic behavior under different operating conditions. The scheme also meets the emulated resistance requirement of LHR with the least total harmonic distortion of 9.88%. Results: The results of the responses of output voltage for the input voltage change and capacitor parameter variation are tabulated as a comparison for the four control scenarios. Of particular interest is the establishment of the fact that conventional SMC technique in which an equivalent switching function ‘ueq’ is generated and compared with a ramp signal in a pulse width modulated (PWM) scheme to generate a constant frequency switching function for DC-DC converters do not apply to LHR so long as the input voltage to the boost converter is a rectified sinusoid. Conclusion: The validity of the analysis is verified through simulation results under MATLAB/ SIMULINK environment.
Keywords: low harmonic rectifiers